Information sources of children (ages 5 to 12) in consumer decision making - Romero, Joanne C.; Reandelar, Joanne F. (2004.)
This study aims to obtain data on the information sources of children age 5 and 12 specifically their internal and external information sources regarding frequent and infrequent purchases. A cross-sectional survey based on a 2 x 2 x 2 factorial design, with two age groups (age 5 and 12), two levels of information sources (internal and external) and two frequencies of purchase (frequent and infrequent, was used. The data was gathered from thirty randomly selected students from Proverbsville School in Angeles City. Fifteen children age 5 and fifteen children age 12 were interviewed on their sources of information in consumer decisions. Based on the response gathered, children generally consult more internal information sources when buying frequently purchased items and more external information sources when buying infrequently purchased items. Older children consult more information sources and consider more factors than younger children. Gender does not have any effect on the information sources of children. The data also implies that the top internal sources of children are from previous experiences with a product and from parents' referrals. The top external information sources are in-store search and parents' referrals. Children do not consider teachers as information sources for their consumer decisions. It is recommended that consumer socialization be developed in an early age, including teaching children how to purchase, what to purchase, what important factors to consider prior to a purchase, and how to discern good from bad quality products. It is also recommended that the information database of young children be developed through the implementation of a curriculum that focuses consumer skills and knowledge, and guidance from parents and other "consumer-literate" adults. Laws and regulations that are specifically focused on the protection of children's consumer rights should also be made.
Thesis (BSHE)--University of the Philippines Diliman.
Keywords: Children as consumers -- Philippines